The Whining Karen meme on X: a semiotic analysis - Yanuar, Rose Mutiara; Agustina, Mia Fitria; Februansyah, Rizki (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2024)
This study conducts a semiotic analysis of the specific "Karen" meme of whining on social media platform X, utilizing Ferdinand de Saussure's semiotic theory. This meme typically depicts a stereotype of a forceful, entitled, and confrontational individual, and it is often linked to middle-aged white women, expanded to encompass various individuals. The findings reveal a consistent pattern of meaning play, revolving around the utilization of the term "Karen" in conjunction with the descriptor "whining." "Karen" is used as a stereotypical reference, often employed to mock individuals perceived as entitled, overly critical, or complaining. It is used to dismiss or undermine the credibility of the opposing viewpoint, implying that the concerns expressed are unwarranted or exaggerated. Overall, the pattern across these conversations highlights the use of Karen memes as a means of ridiculing or dismissing opposing viewpoints perceived as complaining or entitled. This use adds a derisive and somewhat sarcastic tone to the responses, suggesting that the concerns are frivolous or exaggerated. This highlights the complex interplay of language, stereotype, and meaning in internet memes. The results underscore the adaptability and depth of Saussure's theory in deciphering the intricacies of online discourse, particularly within the realm of meme culture.